Transgenic hybrid aspen trees with increased gibberellin (GA) concentrations suggest that GA acts in parallel with FLOWERING LOCUS T2 to control shoot elongation. Issue 3 (10th November 2014) - Eriksson, Maria E.; Hoffman, Daniel; Kaduk, Mateusz; Mauriat, Mélanie; Moritz, Thomas
Summary: Bioactive gibberellins (GAs) have been implicated in short day (SD)‐induced growth cessation in Populus, because exogenous applications of bioactive GAs to hybrid aspens ( Populus tremula × tremuloides ) under SD conditions delay growth cessation. However, this effect diminishes with time, suggesting that plants may cease growth following exposure to SDs due to a reduction in sensitivity to GAs. In order to validate and further explore the role of GAs in growth cessation, we perturbed GA biosynthesis or signalling in hybrid aspen plants by overexpressing AtGA20ox1, AtGA2ox2 and PttGID1.3 (encoding GA biosynthesis enzymes and a GA receptor). We found trees with elevated concentrations of bioactive GA, due to overexpression of AtGA20ox1, continued to grow in SD conditions and were insensitive to the level of FLOWERING LOCUS T2 ( FT2 ) expression. As transgenic plants overexpressing the PttGID1.3 GA receptor responded in a wild‐type (WT) manner to SD conditions, this insensitivity did not result from limited receptor availability. As high concentrations of bioactive GA during SD conditions were sufficient to sustain shoot elongation growth in hybrid aspen trees, independent of FT2 expression levels, we conclude elongation growth in trees is regulated by both GA‐ and long day‐responsive pathways, similar to the regulation of flowering in Arabidopsis thaliana .